Meningkatkan Kinerja Karyawan Melalui Peran Kepemimpinan, Motivasi Dan Disiplin Kerja - Karlina, Indah Ayu; Cahyani, Rusnandari Retno; Paningrum, Destina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
Human resource represents the asset to an organization/company. Existence of Human Resource cant replaced by other resource. Efficacy of Human Resource supported by leadership role, motivation, work discipline and optimalization good performance.Research purpose is to knowing the influence of leadership role, motivation, and work discipline to employee performance Sahid University of Surakarta. Keyword: Leadership Role, Motivation, Work Discipline, Employee Performance